Virus Dynamics Are Influenced by Season, Tides and Advective Transport in Intertidal, Permeable Sediments - Vandieken, Verona; Sabelhaus, Lara; Engelhardt, Tim (Frontiers in Microbiology, 2017)
Sandy surface sediments of tidal flats exhibit high microbial activity due to the fast and deep-reaching transport of oxygen and nutrients by porewater advection. On the other hand during low tide, limited transport results in nutrient and oxygen depletion concomitant to the accumulation of microbial metabolites. This study represents the first attempt to use flow-through reactors to investigate virus production, virus transport and the impact of tides and season in permeable sediments. The reactors were filled with intertidal sands of two sites (North beach site and backbarrier sand flat of Spiekeroog island in the German Wadden Sea) to best simulate advective porewater transport through the sediments. Virus and cell release along with oxygen consumption were measured in the effluents of reactors during continuous flow of water through the sediments as well as in tidal simulation experiments where alternating cycles with and without water flow (each for six hours) were operated. The results showed net rates of virus production (0.3-13.2 x 106 viruses cm-3 h-1) and prokaryotic cell production (0.3-10.0 x 105 cells cm-3 h-1) as well as oxygen consumption rates (56-737 µmol l-1 h-1) to be linearly correlated reflecting differences in activity, season and location of the sediments. Calculations show that total virus turnover was fast with 2 to 4 days, whereas virus-mediated cell turnover was calculated to range between 5-13 or 33-91 days depending on the assumed burst sizes (number of viruses released upon cell lysis) of 14 or 100 viruses, respectively. During the experiments, the homogenized sediments in the reactors became vertically structured with decreasing microbial activities and increasing impact of viruses on prokaryotic mortality with depth. Tidal simulation clearly showed a strong accumulation of viruses and cells in the top sections of the reactors when the flow was halted indicating a consistently high virus production during low tide. In conclusion, cell lysis products due to virus production may fuel microbial communities in the absence of advection-driven nutrient input, but are eventually washed off the surface sediment during high tide and being transported into deeper sediment layers or into the water column together with the produced viruses.